Determinasi Maternal pada Kasus Stunting Balita 6–24 Bulan di Aceh Selatan - Surya Dharma; Ismail Efendy; Aida Fitria (Jurnal Kesehatan Amanah, 2025)
Stunting is a serious public health problem that has a long-term impact on the quality of life of future generations, especially in terms of physical, cognitive, and productivity growth. This study aims to analyze maternal factors that affect the incidence of stunting in toddlers aged 6–24 months in South Aceh Regency, the area with the highest prevalence of stunting in Aceh Province. The research design used a case-control study involving 228 respondents, consisting of 114 stunted toddlers as the case group and 114 non-stunted toddlers as the control group. Data were obtained through maternal health records (KIA book), observations, and e-PPGBM data, then analyzed using multiple logistic regression. The results of the study showed that maternal factors that had a significant effect on the incidence of stunting were the age of at-risk mothers (<20 years or >35 years), the number of children, pregnancy anemia, and chronic energy deficiency (KEK). The SEZ factor during pregnancy was the most dominant determinant with a 4.46 times greater risk of giving birth to stunted children compared to mothers with normal nutritional status (p=0.014; 95% CI=1.35–14.73). These findings confirm the importance of maternal nutrition interventions from pre-conception to pregnancy, optimization of antenatal care (ANC) visits, and appropriate family planning as a stunting prevention strategy based on local contexts.